Finding Common Interests - Yoo, Hee Jeong (Soa--chʻŏngsonyŏn chŏngsin ŭihak = Journal of child & adolescent psychiatry, 2022)
[...]the journal takes an active role in the discussion of clinically relevant and urgent issues. In the same context, for the coming year, our journal is preparing special issues on practice guidelines for autism spectrum disorder and post-COVID-19 school mental health. What I can do as a researcher and editor is establish and elaborate more diverse common interests in our field, fostering more consolidated interchange among researchers and clinicians via the platform of the Journal of KACAP. Besides the manuscripts themselves, any suggestions regarding new research areas, discussions of socially relevant topics, or research subjects for trainees are welcomed and fully considered.